2015
DOI: 10.1002/alr.21666
|View full text |Cite
|
Sign up to set email alerts
|

TAS2R38 genotype predicts surgical outcome in nonpolypoid chronic rhinosinusitis

Abstract: Background Over 550,000 sinus surgeries are performed annually in the United States on patients with chronic rhinosinusitis (CRS). Although the results of sinus surgery vary widely, no known genetic factor has been identified to predict surgical outcomes. The bitter taste receptor T2R38 has recently been demonstrated to regulate upper airway innate defense and may affect patient responses to therapy. Our goal was to determine whether TAS2R38 genetics predicts outcomes in CRS patients following sinus surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
129
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 100 publications
(141 citation statements)
references
References 22 publications
8
129
0
4
Order By: Relevance
“…Furthermore, an additional endotype of CRS has been described, as patients who do not possess the bitter taste receptor T2R38 are at increased risk of failed medical treatment and may have an increased need for surgical intervention. 9 The aim of this systematic review is to examine the evidence regarding use of MAbs in the treatment of CRS.…”
Section: Crs Pathophysiologymentioning
confidence: 99%
“…Furthermore, an additional endotype of CRS has been described, as patients who do not possess the bitter taste receptor T2R38 are at increased risk of failed medical treatment and may have an increased need for surgical intervention. 9 The aim of this systematic review is to examine the evidence regarding use of MAbs in the treatment of CRS.…”
Section: Crs Pathophysiologymentioning
confidence: 99%
“…Genetic variations of the bitter taste receptor TAS2R38, expressed in the cilia of the human sinonasal epithelial cells (HSEC), seem to be associated with susceptibility to upper respiratory tract infections and CRS …”
Section: Introductionmentioning
confidence: 99%
“…A prospective study was conducted from 123 CRS patients undergoing primary FESS with preoperative and 6‐month postoperative Sino‐Nasal Outcome Test (SNOT‐22), a validated patient‐reported measure of sinonasal disease severity; 82 of the patients in the study had nasal polyps and 41 patients were without nasal polyps. In the nonpolyp group, it was demonstrated that homozygotes for the functional receptor (PAV/PAV) had a 6‐month postoperative mean SNOT‐22 score improvement of 38 ± 21; whereas heterozygotes (AVI/PAV) or homozygotes for the nonfunctional receptor (AVI/AVI) had a mean improvement of 12 ± 22 ( P = 0.006) . This data supports the notion that the TAS2R38 genotype is the first genetic polymorphism predictive of surgical outcome for a select group of CRS (nonpolyp) patients.…”
Section: Introductionmentioning
confidence: 99%